2009
DOI: 10.1097/inf.0b013e3181a854ae
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Detection of Human Bocavirus Dna in Nasopharyngeal Aspirates of Children With Respiratory Tract Disease

Abstract: Increasing evidence suggests that the recently identified human bocavirus (hBoV) is a cause of acute respiratory illness. However, the duration of hBoV shedding from the respiratory tract as demonstrated by positive hBoV polymerase chain reaction is unclear. We describe the virologic and clinical characteristics of 6 immunocompetent children with hBoV persistence in the respiratory tract for up to 4.5 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 9 publications
7
49
0
1
Order By: Relevance
“…This might be explained by deficient immune responses in the studied children with wheezing and RV infection (6, 7, 44 The second most common pathogen in asymptomatic infections was HBoV. This is consistent with earlier studies when HBoV has been found in up to 44% of asymptomatic infections with prolonged presence in immunocompetent children and suggests that many asymptomatic HBoV infections are truly asymptomatic (37, 38). Moreover, MPV, EV and CV showed similar prevalence in asymptomatic and symptomatic infections (Online Supplementary, Table S1).…”
Section: Discussionsupporting
confidence: 83%
“…This might be explained by deficient immune responses in the studied children with wheezing and RV infection (6, 7, 44 The second most common pathogen in asymptomatic infections was HBoV. This is consistent with earlier studies when HBoV has been found in up to 44% of asymptomatic infections with prolonged presence in immunocompetent children and suggests that many asymptomatic HBoV infections are truly asymptomatic (37, 38). Moreover, MPV, EV and CV showed similar prevalence in asymptomatic and symptomatic infections (Online Supplementary, Table S1).…”
Section: Discussionsupporting
confidence: 83%
“…[26][27][28][29] However, no evidence of systemic, genuinely long-term (years; decades) persistence exists for HBoV, 30,31 as exists for the other parvovirusesfor B19 in multiple organs [30][31][32] and for parvovirus 4 in lymphoid tissues. 30,[33][34][35] Neither have any data (molecular or serological) been presented to indicate that HBoV secondary infectionsendogenous reactivations or exogenous reinfections -do occur.…”
Section: Discussionmentioning
confidence: 94%
“…HBoV1 DNA may reside in the upper airways for months after acute infection, either due to getting trapped in the nasopharynx, prolonged shedding or mucosal contamination from virus particles in the breathing air [3437]. Similar tissue persistence as that of B19 virus or AAV, has, however, not been detected for HBoV, at least to the same extent [31,3840].…”
Section: Clinical Impact and Epidemiologymentioning
confidence: 99%